Emergency Mode of Control of Rubber Belt Conveyors via PLC System Arduino Opta - Volodya Vladimirov Dzharov (Lamintang Education and Training (LET) Centre, 2025)
The purpose of this article is to investigate emergency modes in conveyor belt technology, focusing on improving protections and interlocks for greater reliability when controlled by the Arduino Opta controller. The operation of a simulation model of a rubber conveyor belt using a programmable logic controller and relay-contactor groups is presented. An experimental study of the operation of a physical model of a rubber belt conveyor was carried out using installed sensors to obtain information about the condition of the facility in real time. This was done simultaneously with the optimization of the parameters of the automation model, after which the analysis and synthesis of the Ladder program for command and control was used. The visualization, based on a programmable logic controller